Upaya Meningkatkan Kemampuan Berbicara Bahasa Indonesia Anak Melalui Metode Bermain Kartu Flashcard - Kadek Suartini; Luh Srinadi; Putu Adi Kristiani; Maria Yustina Nggera Ngaba (Early Childhood Education Development and Studies (ECEDS), 2021)
The problem found in this research is the low ability of children to speak Indonesian. This study aims to determine the increase in the ability to speak Indonesian in group A semester II at the Tigawasa-Buleleng State Kindergarten in the 2021/2022 Academic Year after applying flash card media. This type of research is classroom action research (PTK) which is carried out in two cycles. The research subjects were 12 children in group A semester II at the Tigawasa-Buleleng Village Public Kindergarten for the 2021/2022 Academic Year. Data on the ability to speak Indonesian in group A children was followed by using the observation method with an instrument in the form of an observation sheet. Research data were analyzed using descriptive and qualitative statistical analysis methods. These results indicate that there was an increase in the child's ability to speak Indonesian in cycle 1 of: 55% in the low criteria and in cycle II it increased to 82.55% in the high criteria.